Osr1 Is Required for Mesenchymal Derivatives That Produce Collagen in the Bladder - Vasikar Murugapoopathy (MDPI AG, 2021)
The extracellular matrix of the bladder consists mostly of type I and III collagen, which are required during loading. During bladder injury, there is an accumulation of collagen that impairs bladder function. Little is known about the genes that regulate production of collagens in the bladder. We demonstrate that the transcription factor Odd-skipped related 1 (Osr1) is expressed in the bladder mesenchyme and epithelium at the onset of development. As development proceeds, Osr1 is mainly expressed in mesenchymal progenitors and their derivatives. We hypothesized that Osr1 regulates mesenchymal cell differentiation and production of collagens in the bladder. To test this hypothesis, we examined newborn and adult mice heterozygous for Osr1, Osr1+/−. The bladders of newborn Osr1+/− mice had a decrease in collagen I by western blot analysis and a global decrease in collagens using Sirius red staining. There was also a decrease in the cellularity of the lamina propria, where most collagen is synthesized. This was not due to decreased proliferation or increased apoptosis in this cell population. Surprisingly, the bladders of adult Osr1+/− mice had an increase in collagen that was associated with abnormal bladder function; they also had a decrease in bladder capacity and voided more frequently. The results suggest that Osr1 is important for the differentiation of mesenchymal cells that give rise to collagen-producing cells.